Regulation of plant biotic interactions and abiotic stress responses by inositol polyphosphates - Riemer, Esther; Pullagurla, Naga Jyothi; Yadav, Ranjana; Rana, Priyanshi; Jessen, Henning J.; Kamleitner, Marília; Schaaf, Gabriel; Laha, Debabrata (Frontiers in Plant Science, 2022)
Inositol pyrophosphates (PP-InsPs), derivatives of inositol hexakisphosphate (phytic acid, InsP6) or lower inositol polyphosphates, are energy-rich signaling molecules that have critical regulatory functions in eukaryotes. In plants, the biosynthesis and the cellular targets of these messengers are not fully understood. This is because, in part, plants do not possess canonical InsP6 kinases and are able to synthesize PP-InsP isomers that appear to be absent in yeast or mammalian cells. This review will shed light on recent discoveries in the biosynthesis of these enigmatic messengers and on how they regulate important physiological processes in response to abiotic and biotic stresses in plants.